Elihu Burritt correspondence - Burritt, Elihu, 1810-1879.
ALS (New Britain, Conn.; 1859 July 21) from Burritt concerning a proposal to abolish slavery by providing compensation to slaveholders for the emancipation of their slaves.
Reformer, publisher, and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Slaveholders; Slavery; Slaves -- Emancipation; Authors; Publishers; Reformers